Inclusion of microalga Dunaliella salina in the diet of laying hens: effects on egg quality and sensory traits - Obete Madacussengua; Cátia Falcão Martins; Ana Beatriz Rodrigues Tavares; Daniela Filipa Pires Carvalho; Ana Rita Mendes; Tiago Guerra; António Pagarete; Suzana Ferreira-Dias; Miguel Pedro Mourato; José António Mestre Prates; André Martinho de Almeida; Madalena Lordelo (Algal Research, 2026)

Northern shrimp exhibit origin-specific proteomic remodelling under ocean acidification, with limited response to ocean warming - Tessa M. Page; Miguel Rosado; Vera M. Mendes; Ella Guscelli; Joana Filipa Fernandes; Denis Chabot; Ricardo Calado; Bruno Manadas; Piero Calosi; Diana Madeira (Marine Pollution Bulletin, 2026)

C. elegans as a powerful model for neurotoxicity assessment - Daniel José Barbosa; Inês C. Santos; Tatiana Moyisyeyenko; Cristina Mendes; Ana Filipa Sobral (NeuroToxicology, 2025)

A versatile yeast model identifies the pesticides cymoxanil and metalaxyl as risk factors for synucleinopathies - Leslie Amaral; Filipa Mendes; Manuela Côrte-Real; António Rego; Tiago F. Outeiro; Susana R. Chaves (Chemosphere, 2024)

Cellular Aging Secretes: a Comparison of Bone-Marrow-Derived and Induced Mesenchymal Stem Cells and Their Secretome Over Long-Term Culture - Ana Marote; Diogo Santos; Bárbara Mendes-Pinheiro; Cláudia Serre-Miranda; Sandra I. Anjo; Joana Vieira; Filipa Ferreira-Antunes; Joana Sofia Correia; Caroline Borges-Pereira; Andreia G. Pinho; Jonas Campos; Bruno Manadas; et al. (Stem Cell Reviews and Reports, 2023)

Movements of Hatchery-Reared Dusky Groupers Released in a Northeast Atlantic Coastal Marine Protected Area - Ana Filipa Silva; Bárbara Horta e Costa; José Lino Costa; Esmeralda Pereira; João Pedro Marques; João J. Castro; Pedro G. Lino; Ana Candeias-Mendes; Pedro Pousão-Ferreira; Inês Sousa; Luís Bentes; Jorge M. S. Gonçalves; et al. (Journal of Marine Science and Engineering, 2022)
No-take areas are key instruments to promote the effectiveness of Marine Protected Areas (MPAs), particularly concerning the protection of endangered species such as the dusky grouper (Epinephelus marginatus). However, despite the establishment of no-take areas and the prohibition of catching this species in a southwestern Portuguese MPA (SACVMP—‘Sudoeste Alentejano’ and ‘Costa Vicentina’ Marine Park) since 2011, there is still no evidence of population recovery. By using acoustic biotelemetry, this work aimed to evaluate the feasibility of restocking hatchery-reared adult dusky groupers in two no-take areas within the SACVMP. In 2019 and 2021, thirty groupers were tagged with acoustic transmitters and the site attachment and movements of the groupers were assessed in the releasing sites (no-take areas). None of the tagged fish settled down in either of the areas, leaving the no-take areas mainly at dusk and night. Some individuals displayed extended movements of more than a hundred kilometers along the Portuguese coast which was rarely reported for this species. At least in some coastal stretches, those movements were performed close to the shore, which may evidence the importance of coastal MPAs to protect and promote the connectivity of species more associated with rocky reef habitats. Following studies should focus on the conditions that promote site attachment and fidelity by hatchery-reared dusky groupers so that future large-scale restocking programs can be successful in MPAs with appropriate habitats.

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Unravelling the antitumoral potential of novel bis(thiosemicarbazonato) Zn(II) complexes: structural and cellular studies - Elisa Palma; Hugo M. Botelho; Goreti Ribeiro Morais; Inês Rodrigues; Isabel Cordeiro Santos; Maria Paula Cabral Campello; Paula Raposinho; Ana Belchior; Susana Sousa Gomes; Maria Fátima Araújo; Isabel Correia; Nadia Ribeiro; et al. (JBIC Journal of Biological Inorganic Chemistry, 2019)

Anticancer activity of structurally related ruthenium(II) cyclopentadienyl complexes - Leonor Côrte-Real; Filipa Mendes; Joana Coimbra; Tânia S. Morais; Ana Isabel Tomaz; Andreia Valente; M. Helena Garcia; Isabel Santos; Manuel Bicho; Fernanda Marques (JBIC Journal of Biological Inorganic Chemistry, 2014)

Study of the synthesis, antiproliferative properties, and interaction with DNA and polynucleotides of cisplatin-like Pt(II) complexes containing carcinogenic polyaromatic amines - Elisabetta Gabano; Sofia Gama; Filipa Mendes; Marzia B. Gariboldi; Elena Monti; Sophie Bombard; Sabrina Bianco; Mauro Ravera (JBIC Journal of Biological Inorganic Chemistry, 2013)

Effects of dietary arachidonic acid on cortisol production and gene expression in stress response in Senegalese sole (Solea senegalensis) post-larvae - Dulce Alves Martins; Filipa Rocha; Filipa Castanheira; Ana Mendes; Pedro Pousão-Ferreira; Narcisa Bandarra; Joana Coutinho; Sofia Morais; Manuel Yúfera; Luís E. C. Conceição; Gonzalo Martínez-Rodríguez (Fish Physiology and Biochemistry, 2013)